Antagonistic Actions of Escherichia coli, Faecal Streptococci and Natural Bacterial Flora on Staphylococcus aureus in Shrimp Homogenate - T.S., Gopalakrishna Iyer; K.P., Shrivastava (Fishery Technology, 2025)
The antagonistic effect of Escherichia coli, faecal streptococci and natural bacterial flora on Staphylococcus aureus in shrimp homogenate was studied at 28, 10 and 0oC. It was observed that staphylococci could not grow in competition with E. coli, faecal streptococci and natural bacterial flora at any of the temperatures studied.